EVALUATION OF ENTOMOPATHOGEN Verticillium lecanii IN CONTROL OF THE APHID Mvzus persicae IN CHRYSANTHEMUMS - HINCAPIE-V., ROSALBA; OSPINA-Z., HENRY A.; BUSTILLO-P., ALEX E.; SALDARRIAGA-V., ALFREDO (Revista Colombiana de Entomología, 1990)
Chrysanthemum crops in Colombia are attacked by a great variety of insects and diseases which cause serious problems with the flower quality and create quarantine restrictions at the time of export. The green peach aphid, Myzus persicae (Sulzer) is one of these pests in which growers are expending a considerable amount of money in its control using chemical products that in turn cause insect resistance, biological disturbances, environmental pollution, and hazards. This research had the objective to explore the possible use of the entomopathogen Verticillium lecanii (Zimm.) Viegas against M. persicae in that ecosystem. Three native strains of this fungus were used: an M. persicae strain (VL-A), another insolated from Erinnyisello L. (VL-GC), and a third from Trialeurodes vaporariorum (Westwood) (VL-MB). These strains were tested at a concentration of 1x108 conidia/ml against M. persicae reared in radish plants. The VL-A strain was the most pathogenic causing total mortality of 100%, while VL-GC and VL-MB caused 37.5% and 30% mortality, respectively. When the VL-A strain was evaluated at three concentrations (1x104, 1x106, 1x108 e/mi) on aphis reared on radish plants, it was observed that mortality increased as concentration was higher from 39.5% to 100%. The environmental conditions of this study were 22°C (19.3 - 26.0°C) and 91% RH (70.2 -99.6% ). When this same experiment was performed in a commercial chrysanthemun greenhouse crop, the results varied due to adverse environmental conditions of 16.2°C (10,8 - 28.5°C) and 78.7°i RH (38.7 - 96%). Temperature was high during the day and hudity low while at night the contrary occurred. Spraying the fungus three times at intervals of eight days a mortality of 76.2% was obtained with the highest concentrations. This study allows us to conclude that V. lecanni could be useful in these flower crops if humidity conditions are high (> 90% RH) during critical periods of infections and conidiogenesis.